The Notary's Liability Who Participated Doing Unlawful Acts in Making The Deed of Guarantee Submission Agreement Based on The Case Study of Decision Number 61/PDT.G/2019/PN.GIN - Bedita Putri Sa’idah; Pieter Everhardus Latumeten (LEGAL BRIEF, 2022)
A notary is a public official who is authorized by the state to make an authentic deed. If one of the parties feels aggrieved by the deed made by the Notary, that party can sue the Notary for the unlawful act committed. Notaries as public officials who have an important role in people's lives. In carrying out his position, it is not enough for a Notary to only have legal expertise but must also be based on responsibility and appreciation of the nobility of dignity and ethics. Its role and authority are very important for legal traffic in society. Therefore, a notary must carry out his profession professionally, highly dedicated and uphold the dignity and worth of by upholding the code of ethics of a notary. By enforcing the notary's code of ethics, it is very important for the notary to better understand the extent to which the act can be regarded as a violation of the code of ethics, and provide education so that things do not happen that can harm the notary and the community he serves. This study aims to examine the accountability of the Notary to the deed of guarantee delivery agreement that he has made based on Decision Number 61/Pdt.G/2019/PN.Gin. This research uses In this study the legal research method used is normative juridical. The approach used is a statutory approach. The analytical method used is qualitative, and the results of the research used are analytical explanatory. The findings in this study are the responsibility of the notary in making the guarantee agreement deed, proven to have committed an unlawful act and violated the provisions of Article 1365 of the Civil Code. The legal consequences given are the cancellation of the deed and dishonorable dismissal. It is recommended that the notary be more careful in making the deed so that problems do not occur in the future.